PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN TEMATIK MENGGUNAKAN TIPE MAKE A MATCH DI KELAS III SEKOLAH DASAR BAWAMAI - Firalina, Firalina; Asran, Mastar; Margiati, KY. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research to describe the improvement of teachers' ability in planning and implementing learning, as well as learning outcomes by applying the Make A Match model on thematic learning in the third grade of Bawamai Elementary School. Technique of collecting data in the form of direct observation and test. The results obtained in this research are: (1) The planning of thematic learning with type Make A Match has been designed in accordance with IPKG 1 and can improve learners' learning outcomes. (2) The implementation of thematic learning with the type of Make A Match that has been implemented on the students in the third grade of private elementary school bawamai Pontianak has been implemented in accordance with the program established BNSP include: content, materials, learning process, human resources, facilities and infrastructure, assessment (process / outcome). (3) There is improvement of learning result can be seen from result of final test which observed with two cycles that is on cycle I mean result of test of learner 61,18 and in cycle II average test result equal to 81,62Â Keywords : Tematic Learning, Make A MatchÂ